The role and treatment potential of natural killer T (NKT) cells in patients with upper gastrointestinal cancers - MELO RODRIGUEZ, ASHANTY MAGGVIE (Trinity College Dublin. School of Medicine. Discipline of Immunology, 2019)
Oesophageal adenocarcinoma (OAC), squamous cell carcinoma (SSC) and gastric cancers (GAC), collectively cause over 1.3 million deaths worldwide reported in 2018. Current therapeutic regimens focus on chemo-radiotherapy prior to surgery, however, only 20-30% of patients respond to treatment. Therefore, new treatments are urgently required. Invariant natural killer T (iNKT) cells are innate T cells with semi-invariant T cell receptors that recognise glycolipids presented by CD1d. iNKT cells have antitumour activities that are currently being tested as cellular therapies iNKT cell frequencies were quantified in pre- and post-treatment blood and omentum from 152 patients with GAC, SCC or OAC by flow cytometry. They were found to be depleted in peripheral blood from GAC, SCC and OAC patients compared to controls. Omentum had higher frequencies of iNKT cells in the cancer patients compared to blood. These findings suggest that iNKT cells may mediate immunity against GAC, SSC and OAC and that the omentum could be a source of cells for use in adoptive cell therapy. Since clinical trials involving iNKT cells in other cancers have to date shown limited clinical efficacy, we investigated if the antitumour activities of these cells could be improved by coordinating treatment with current chemotherapy and radiotherapy regimens or by the use of alternative glycolipid ligands. iNKT cells were isolated from healthy donor blood samples and expanded in vitro. They were treated with various concentrations of cisplatin, carboplatin, paclitaxel, 5-fluorouracil for 24 or 48h or irradiated with a single dose of 2 Gy or 10 Gy or five fractionated doses of 2 Gy. Cells were then assayed for viability, apoptotic markers, or co-cultured with CD1d transfected HeLa cells pulsed with the iNKT cell agonist ligand, α-galactosylceramide (α-GalCer), for assays of cytolytic degranulation and intracellular cytokine, granzyme B and perforin production. Cisplatin, 5-FU, carboplatin, paclitaxel and radiation exhibited a dose-dependent inhibition of iNKT cell viability. Cisplatin also inhibited degranulation and IFN-γ, but not IL-4, production by viable iNKT cells. While 5-FU, carboplatin, paclitaxel and radiation increased apoptosis of iNKT cells, it did not affect activation. A number of synthetic glycolipids analogues of α-GalCer were also tested for their ability to bind to CD1d-transfected HeLa cells and activate the antitumour activities of iNKT cells. One novel glycolipid, XZ7, induced cytolytic degranulation and IFN-γ production by CD8+ and double negative iNKT cells, suggesting that it may be superior to α-GalCer as a lead compound for activating the antitumour activities of iNKT cells. We also tested for the presence of non-invariant (type II) NKT cells reactive against a number of glycolipids that were previously shown to bind to CD1d and stimulate T cells, in OAC patients and control subjects. OAC patients had higher frequencies of sulfatide and tetramyristoyl-cardiolipin (TO CL)-specific T cells compared to controls. Most of these cells expressed the Vδ1 T cell receptor. TO CL induced the production of transforming growth factor-β by expanded Vδ1 T cells in vitro. Low iNKT cell and high type II NKT cell numbers may predispose individuals to upper gastrointestinal cancers and boosting iNKT cell numbers may have therapeutic value. However, exposure to systemic chemotherapy can negatively affect their functions and should be considered when developing iNKT cell-based immunotherapies.
APPROVED
Keywords: Oesophageal cancer; Gastric cancer; NKT cells; Glycolipids; Radiotherapy; Chemotherapy; CD1d